STRESS REVIEW FROM CAREER MOTHERS WHO HAVE CHILDREN AGED 11-13 YEARS OLD IN MOJOPANGGUNG KELURAHAN RT 01 / RW 01 SUB-DISTRICT GIRI, BANYUWANGI REGENCY - Eni Jumaro; Sadi (International Jurnal of Education Schoolars, 2022)
The stress felt by career mothers is caused by two responsibilities that must be carried out simultaneously, namely women are required to be responsible for their work, and take care of their household. This study aims to determine what factors cause stress in career mothers, to find out the efforts made by career mothers in dealing with stress and to determine the success of career mothers in Mojopanggung Village, RT 01 / RW 01, Giri District, Banyuwangi Regency in dealing with the stress they feel.. The type and research approach in this study used qualitative methods with a descriptive approach. The participants of this study were career mothers aged approximately 30-60 years, had children aged 11-13 years, women who worked for more than 1 year. with the number of working hours 20-40 hours per week. The results of this study indicate that the four subjects feel stressed, the factors that cause stress include problems at work such as, the amount of work that makes them tired and thinking, causing frustration for career mothers, followed by family problems with family problems such as problems in intimate relations with husbands. , conflicts with husbands or children and financial problems and the efforts made in overcoming stress by the four subjects succeeded in overcoming stress, including, praying, sincerely, taking a walk (refreshing), taking a short break, solving problems that are being experienced, and build good communication with customers.